The Influence of Halal Labels and Product Quality on Purchasing Decisions at MomQil Frozen Food with Consumer Trust as an Intervening Variable - Nuzula Dzikrina; Abdul Rahman; Muhammad Nasri Katman; Khairunnisa (www.amertainstitute.com, 2024)
Amid the increasing demand for quality halal products, halal labels and product quality have emerged as factors that shape consumer purchasing decisions. This study aims to analyze the influence of halal labels and product quality on purchasing decisions at MomQil Frozen Food, with consumer trust as an intervening variable. Halal labels are an important factor that guarantees the validity and halal quality of products, while product quality includes taste, safety, and cleanliness standards that are expected to increase consumer trust. Because the consumer population of MomQil Frozen Food is not known with certainty or is very broad, sampling was carried out using the Jacob Cohen formula. This study involved 204 respondents who were selected using purposive sampling techniques and analyzed using the Structural Equation Modeling (SEM) method through SmartPLS. The results showed that product quality had a significant effect on purchasing decisions, while halal labels did not have a direct effect. However, consumer trust mediates the effect of halal labels on purchasing decisions. Trust is also able to mediate the effect of product quality on purchasing decisions. These findings indicate that building consumer trust through product quality and halalness is an important strategy to improve purchasing decisions